Direct and mediation effect of supply chain complexity drivers on supply chain performance: an empirical evidence of organizational complexity theory - Chand, Pushpendu; Kumar, Anil; Thakkar, Jitesh; Ghosh, Kunal (Emerald, 2022)
Purpose: In today's globalized business environment, growing supply chain complexity (SCC) is arguably a major threat to the firm's business continuity with an adverse impact on the firm's competitive advantage and business performance. Researchers, though, investigated the impact of SCC drivers on a firm's operational performance, but the key question "Which supply chain complexity drivers severely impact the supply chain performance (SCP)?" remains largely unanswered from empirical research. The present study decomposes the SCC into four major constituting sub-categories (upstream, operational, downstream, and external) to explore the causal impact of SCC drivers on SCP in direct and mediated manner.